2018
DOI: 10.1158/1538-7445.am2018-33
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 33: Calsequestrin 2 regulates proliferation, migration, and invasion in triple-negative breast cancer cells

Abstract: Triple-negative breast cancer (TNBC) is the most heterogeneous and aggressive breast tumor subtype defined by absence of receptor for estrogen, progesterone, or HER2. However, the biologic mechanism for TNBC phenotype is still unclear. Here, we show that expression of Calsequestrin 2 (CASQ2), a Ca2+-binding protein, correlates with increase of proliferation, migration, and invasion, suggesting that intracellular Ca2+ may contribute to tumor growth and metastatic phenotype. CASQ2 is the main Ca2+-binding protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Several FDA-approved anticancer agents (such as 5-fluorouracil, cisplatin, tamoxifen, paclitaxel, and doxorubicin) and drugs against other disease conditions (such as leflunomide, tolvaptan, and teriflunomide) can impact Ca 2+ signaling machinery [ 484 , 485 ]. Some of these drugs, formulated as prodrugs or nanocarrier loads, are under investigation as antagonists of cancer-promoting Ca 2+ signaling See Figure 12 [ 46 , 226 , 227 , 252 , 440 , 441 , 486 , 487 , 488 , 489 , 490 , 491 , 492 , 493 , 494 , 495 , 496 , 497 , 498 , 499 , 500 , 501 , 502 , 503 , 504 , 505 , 506 , 507 , 508 , 509 , 510 , 511 , 512 , 513 , 514 , 515 , 516 , 517 , 518 , 519 , 520 , 521 , 522 , 523 , …”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Several FDA-approved anticancer agents (such as 5-fluorouracil, cisplatin, tamoxifen, paclitaxel, and doxorubicin) and drugs against other disease conditions (such as leflunomide, tolvaptan, and teriflunomide) can impact Ca 2+ signaling machinery [ 484 , 485 ]. Some of these drugs, formulated as prodrugs or nanocarrier loads, are under investigation as antagonists of cancer-promoting Ca 2+ signaling See Figure 12 [ 46 , 226 , 227 , 252 , 440 , 441 , 486 , 487 , 488 , 489 , 490 , 491 , 492 , 493 , 494 , 495 , 496 , 497 , 498 , 499 , 500 , 501 , 502 , 503 , 504 , 505 , 506 , 507 , 508 , 509 , 510 , 511 , 512 , 513 , 514 , 515 , 516 , 517 , 518 , 519 , 520 , 521 , 522 , 523 , …”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In addition, a recent study revealed that B cells are associated with survival and immunotherapy response in sarcoma, and both JCHAIN (also known as IGJ) and TNFRSF17 (encoding BCMA) in tumors may contribute to the improved prognosis 33 . Interestingly, majority of the eight genes in cluster_4 have been reported to be involved in arteriogenesis, 46 migration/invasion, and metastasis in head and neck cancers 47–49 or other tumors 50–53 . In addition, some of the genes may play opposite roles in different tumors.…”
Section: Discussionmentioning
confidence: 99%